An unsymmetric 8-node plane element immune to mesh distortion for linear isotropic hardening material - Chen, Xiaotian (2022)
An 8-node quadrilateral plane element US-QUAD8 is developed for linear isotropic hardening material in the framework of updated Lagrangian unsymmetric finite formulation where (Formula presented.) matrix is constructed by classical shape function, and (Formula presented.) matrix by the higher-order Lagrangian basis function in global coordinate system. The present element eliminates the influence of Jacobian in the elemental stiffness matrix and guarantees the quadratic completeness of displacement field even under severe distorted mesh. Two typical problems meshed with angular/curved-edge/mid-side distorted elements demonstrate excellent performance of distortion resistance of the present element and good computational efficiency in severe mesh distortion.